2021
DOI: 10.4236/ajps.2021.129094
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Cherry (<i>Prunus avium</i> L.) Fruit Drop Reduction by Plant Growth Regulators (Naphthalene Acetic Acid NAA and Gibberellic Acid GA<sub>3</sub>)

Abstract: This study was conducted during 2019/2020 on sweet cherry trees (Prunus Avium L.) (Bing and Hardy Giant) cultivar planted at Sergaya-Al_Zabadani area of Rural Damascus, to reduce fruit drop of sweet cherry. The experiment included 4 foliar applications: T1: control, T2: GA 3 (100 ppm), T3: NAA (20 ppm), T4: (100 ppm GA 3 + 20 ppm NAA). Fruit set and fruit drop percentage, fruiting factor, and yield were recorded. The results showed that treatment with (100 ppm GA 3 + 20 ppm NAA) recorded higher fruit set perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…Aplikasi ZPT jenis auksin dalam penelitian ini menggunakan Napthalene Acetic Acid (NAA). Napthalene Acetic Acid dapat meningkatkan hasil, total padatan terlarut, kadar gula total dan warna buah yang mencolok pada ceri (Askarieh et al, 2021) dan buah jambu biji (Khandakeer, 2017). Selain itu, NAA dapat memengaruhi meningkatnya pembungaan apel (Nizar et al, 2020).…”
Section: Pendahuluanunclassified
“…Aplikasi ZPT jenis auksin dalam penelitian ini menggunakan Napthalene Acetic Acid (NAA). Napthalene Acetic Acid dapat meningkatkan hasil, total padatan terlarut, kadar gula total dan warna buah yang mencolok pada ceri (Askarieh et al, 2021) dan buah jambu biji (Khandakeer, 2017). Selain itu, NAA dapat memengaruhi meningkatnya pembungaan apel (Nizar et al, 2020).…”
Section: Pendahuluanunclassified
“…Apart from exogenous application of GA 3 and 2,4-D, spraying naphthaleneacetic acid (NAA) has also been used to control fruit drop in most fruit trees. Exogenous application of 20 ppm NAA reduced fruit drop in sweet cherries [10].…”
Section: Introductionmentioning
confidence: 95%
“…GA 3 plays an important role in the growth and development of fruit trees and is widely used for increasing yield and fruit retention [9]. Studies have shown that exogenous application of GA 3 significantly delays the abscission of citrus and sweet cherry fruits [10,11]. The correlation between endogenous auxin levels and fruit abscission has been demonstrated in research [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sweet cherries in China are generally grown in the north because the unique climate and environmental factors in the south make it difficult for sweet cherries to bear fruit. In response to this phenomenon, farmers have started spraying GAs, and while the fruit-setting rate of the sweet cherry has been significantly improved [ 3 ], there has been an increase in the prevalence of malformed fruit. The formation of malformed fruits has adversely affected the economic benefits of fruit sales, but the molecular mechanism behind this phenomenon is still unclear.…”
Section: Introducementioning
confidence: 99%